2019
DOI: 10.1038/s41598-019-46643-5
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Spectroscopy-based Metabolomic Biomarkers for Typing, Staging, and Survival Estimation of Early-Stage Human Lung Cancer

Abstract: Low-dose CT has shown promise in detecting early stage lung cancer. However, concerns about the adverse health effects of radiation and high cost prevent its use as a population-wide screening tool. Effective and feasible screening methods to triage suspicious patients to CT are needed. We investigated human lung cancer metabolomics from 93 paired tissue-serum samples with magnetic resonance spectroscopy and identified tissue and serum metabolomic markers that can differentiate cancer types and stages. Most in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
34
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 36 publications
4
34
1
Order By: Relevance
“…But unlike our study, the samples in their research were not plasma, but cancerous cell lines. This may be the main reason for the different results from our study, because differences in the levels of low-molecular metabolites in cancer cells are generally more pronounced than differences in plasma [39]. Tao Wen et al [40] found signi cant differences in plasma levels of some low-molecular metabolites between early adenocarcinoma and healthy people, but the authors did not compare adenocarcinoma with other pathological types of lung cancer.…”
Section: Discussioncontrasting
confidence: 59%
“…But unlike our study, the samples in their research were not plasma, but cancerous cell lines. This may be the main reason for the different results from our study, because differences in the levels of low-molecular metabolites in cancer cells are generally more pronounced than differences in plasma [39]. Tao Wen et al [40] found signi cant differences in plasma levels of some low-molecular metabolites between early adenocarcinoma and healthy people, but the authors did not compare adenocarcinoma with other pathological types of lung cancer.…”
Section: Discussioncontrasting
confidence: 59%
“…So far in only one study, both tissue and plasma from the same population were studied together. Berker et al examined paired tissue and serum samples from 93 patients showing a panel of metabolites indicating the survival time of patients in the early stage of NSCLC [27].…”
Section: Discussionmentioning
confidence: 99%
“…PLS-DA analyzes were able also effectively distinguish the metabolic profile of serum in nonsmall-cell lung carcinoma patients with or without microwave ablation treatment from that of healthy controls [10]. Recently, Berker et al published extended study where NMR spectra of measured matched tissue and serum samples were used also for typing, staging and survival estimation of early stages of lung cancer [11]. Despite the rapid growth of metabolomic studies, only a little part of them uses receiver operator characteristics (ROC) curve analysis as the standard method for describing and accessing the performance of medical diagnostic tools [12].…”
mentioning
confidence: 99%